A rare clinical case of the patient with pulmonary hypertension associated with hereditary hemorrhagic telangiectasia. Case report - Anna M. Kasparova; Zarina S. Valieva; Tamila V. Martynyuk (Терапевтический архив, 2022)
The article describes a rare clinical case of the patient with pulmonary hypertension associated with hereditary hemorrhagic telangiectasia and discusses the issues of the treatment choice of these patients. The presented clinical case is of interest because pulmonary hypertension was initially revealed, then its hereditary nature was confirmed and OslerWeberRendu disease was diagnosed.